Banks as the Actors of a Modern Monetary Policy in Russia: Effects of Exposure on the Econom - Marina, Abramova; Svetlan, Dubova; Vladimir, Maslennikov (Journal of Reviews on Global Economics, 2018)
The article’s relevance is determined by the fact that in the conditions of a bank-oriented financial system the "signals" from the central bank regarding decisions about the monetary policy go to the economy via banks, through which the main channels of the transmission mechanism of the monetary policy are implemented. The analysis of the effects of banks as the actors of the monetary policy is therefore relevant. The article, based on a study of the elements of investment potential for their impact on GDP, contains conclusions about the possibility of achieving economic growth as one of the strategic goals the monetary policy through the main channels of the transmission mechanism using its standard tools. The article is to identify and quantify the factors that have significant effects on economic growth through the impact on investment potential. The change in the Bank of Russia’s key interest affects only some of the investment potential elements such as deposits of legal entities in rubles. Such impact can slightly improve GDP. The use of monetary policy tools will enable the influence on the change of the nominal interest rate and, therefore, the adjustment of real rates, and it may also affect aggregate demand (consumption and investment potential).